Surgical closure of the left atrial appendage in cardiac surgery: a review article - Rojas Sánchez, Pedro Iván (2024)
Surgical occlusion of the left atrial appendage during cardiac surgery has been shown to significantly reduce the risk of stroke and systemic embolism in patients with atrial fibrillation and is currently a procedure with a high degree of recommendation. As cardiovascular surgeons we have the opportunity to offer this additional impactful surgical procedure, so the objective of this review is to understand its anatomical and surgical principles, in addition to evaluating the evidence that supports its indication.